Long non-coding RNA PVT1 promotes tumor progression by regulating the miR-143/HK2 axis in gallbladder cancer - Chen, Jianan; Yu, Yan; Li, Hua; Hu, Qiuyue; Chen, Xiaolong; He, Yuting; Xue, Chen; Ren, Fang; Ren, Zhigang; Li, Juan; Liu, Liwen; Duan, Zhenfeng; et al. (Molecular cancer, 2019)
The long non-coding RNA PVT1 (lncRNA PVT1) has been reported to act as an oncogenic regulator of several cancers. However, its expression and function in gallbladder cancer (GBC) remain largely unknown. In situ hybridization (ISH) and quantitative real-time PCR (qPCR) were performed to detect the expression of PVT1 and miR-143 in GBC tissues and cell lines. Immunohistochemistry (IHC) assays were performed to assess the expression of the hexokinase 2 (HK2) protein. The relationships among PVT1, miR-143 and HK2 were evaluated using dual-luciferase reporter, RNA immunoprecipitation (RIP) and biotin pull-down assays. The biological functions of PVT1, miR-143 and HK2 in GBC cells were explored with cell counting kit 8 (CCK-8), 5-ethynyl-20-deoxyuridine (EdU), colony formation, transwell, wound healing and glucose metabolism assays in vitro. For in vivo experiments, a xenograft model was used to investigate the effects of PVT1 and HK2 on GBC. PVT1 was upregulated in GBC tissues and cells and was positively associated with malignancies and worse overall survival. PVT1 knockdown inhibited cell proliferation, migration, and invasion in vitro and restrained tumor growth in vivo. Further studies demonstrated that PVT1 positively regulated HK2 expression via its competing endogenous RNA (ceRNA) activity on miR-143. Additionally, HK2 expression and function were positively correlated with PVT1. Furthermore, we observed that the PVT1/miR-143/HK2 axis promoted cell proliferation and metastasis by regulating aerobic glucose metabolism in GBC cells. The results of our study reveal a potential ceRNA regulatory pathway in which PVT1 modulates HK2 expression by competitively binding to endogenous miR-143 in GBC cells, which may provide new insights into novel molecular therapeutic targets for GBC.